A rare case of ruptured ovarian ectopic pregnancy in a rural setup - Limbu, Adarsh (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Ovarian ectopic pregnancy is a rare and life-threatening condition, accounting for 0.5% to 3% of all ectopic pregnancies. Due to its nonspecific presentation and diagnostic challenges, early recognition is often delayed, leading to increased morbidity. This is a case of a 37-year-old female presenting with lower abdominal pain and vaginal bleeding. Clinical examination and transabdominal ultrasound suggested a ruptured ectopic pregnancy. Emergency laparotomy confirmed ruptured ovarian ectopic pregnancy, necessitating a left oophorectomy with salpingectomy. The patient had an uneventful recovery. This case underscores the importance of clinical acumen in diagnosing ovarian ectopic pregnancy in resource-limited settings and highlights the critical role of early resuscitation and surgical intervention in reducing mortality and morbidity.